Carnivorous sponges of the Atlantic and Arctic Oceans. Phylogeny, taxonomy, distribution and microbial associations of the Cladorhizidae (Demospongiae, Poecilosclerida) - Hestetun, Jon Thomassen (Journal of the Marine Biological Association of the United Kingdom, 2016)
The sponges (phylum Porifera) are defined by the presence of an aquiferous system in which choanoflagellate cells create a current and filter water flowing through the sponge body. The carnivorous sponges represent the only known exception to filter feeding within the phylum, and instead are able to capture prey including small crustaceans and larval plankton, using a combination of an adhesive surface and numerous filaments suitable for entangling prey. Mobile cells are able to slowly cover prey entangled on the surface of the sponge, and prey items are encapsulated and digested in a process that can last several days. The aquiferous system is either strongly reduced or entirely absent in the carnivorous sponges, which typically have an erect pennate, branching or stipitate pedunculate morphology. Carnivory is usually considered an adaptation to deep-sea conditions, where filter feeding is less efficient due to a lower density of suspended particulate matter. An exceptional evolutionary innovation within the phylum, sponge carnivory was not properly known to science until 1995. Interest in carnivorous sponges have been high in recent years, and over 150 species are currently considered valid, up from some 90 known species at the turn of the millennium. Carnivorous sponges are found within the demosponge order Poecilosclerida, defined by the presence of skeletal chela microsclere spicules. Almost all carnivorous sponges have traditionally been assigned to Cladorhizidae, with a few species assigned to Guitarridae (Euchelipluma) and Esperiopsidae (five Esperiopsis spp.). As spicule morphology is the main diagnostic character in sponge systematics, the large diversity of chela forms found within the genera assigned to Cladorhizidae implies the possibility that the family is polyphyletic, and that carnivory has evolved in several independent poecilosclerid lineages. On the other hand, recent molecular studies have shown that spicule morphology is often more plastic and intricate than previously believed. Thus the ...